Life in the ‘Hum’: Belongings and Everyday Dispossession - Marina Chavez; Terri Evans; Claire Shapton; Alexandra Flynn; Marie-Eve Sylvestre; Nicholas Blomley (International Journal on Homelessness)
Precariously homed people do not control the spaces they call home. As a result, their belongings are governed by the actions of people granted greater legal powers. To fully understand the practice and effects of such regulations requires a community-engaged research methodology. In this paper, we focus on Abbotsford, in British Columbia, Canada, centring the experience of precariously homed people. Regulation of belongings is described by one of our collaborators as the ‘hum’: an omnipresent experience of property dispossession and devaluation. We explain the hum’s pervasiveness and scope, grounding it in particular forms of urban-legal governance, property law, and hierarchical (de)valuation. We trace its violent and traumatizing effects, noting the way it intensifies vulnerability.